Trade linkages between Malaysia and the OIC member countries: Empirical evidence based on gravity model - Zainal Abidin, Irwan Shah; Jantan, Mohd Dan; Mohd Satar, Nurulhuda; Haseeb, Muhammad (Science Publications, 2014)
This study examines trade relations between Malaysia and 55 of the Organization of Islamic Cooperation (OIC) member countries for the period of 1995 to 2012. Applying the Trade Gravity Model (TGM), the study will isolate factors that determine Malaysia-OIC trade measured by Malaysian exports to OIC member countries.Since the series are integrated of order 1 and appear to be cointegrated, we utilize the Fully Modified OLS (FMOLS) to estimate the determinants of trade between Malaysia and OIC countries.The FMOLS estimation reported that per capita GDP, Foreign Direct Investment (FDI) differential and real exchange rate of OIC member countries are supporting the expansion of the exports whereas any increase in trade per GDP ratio, corruption and real exchange rate of Malaysia creates additional impediments to the trade relation.The findings suggest that economic strengthening as the basis for increase in trade between Malaysia and OIC members.Investment appears to be complementary to the trading relations in the Malaysia-OIC case.The social capital also plays role in supporting the trade.